Does Global Leadership Development Boost Multinational Corporations (MNCs) Performance? - Chongcharoen, Duangkamol; Khan, Muhammad Shahid; Jankaweekun, Premkamon (Journal of Innovation and Management, 2020)
As organisations continue to expand globally, the limelight is more and more concentrated on how to lead and develop a diverse multinational group of people as well as understand the cultural idiosyncrasies of each new market. A survey reported in the Society for Management concluded that “42% of leaders failed when sent abroad on a leadership assignment, the main reasons reported were a lack of language and cultural awareness skills, and a lack of a global mindset” (Buckby, 2015). To overcome global challenges such as; global economic crises, cultural barriers, knowledge, and skills shortage, a leader’s development is the only solution to avoid global failure. This article reveals that a leadership development program can enhance the Multinational Corporation (MNC) performance. This article discusses the importance of leadership development and its association with organisational development. As a leader of MNC operates in different countries, where, he/she suffers from different challenges.